Path Data in Marketing: A Case Study of Broiler Chickens’ Partnership System in Kediri Regency, Indonesia - Nanang Febrianto; Budi Hartono; Anie Eka Kusumastuti; Puji Akhiroh (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2022)
The study aimed to determine the distribution and marketing channels of the broiler chickens’ partnership system in Kediri Regency, Indonesia. Data were collected from July to August 2020. The respondents used in this study were plasma farmers and marketing agencies involved in the marketing of broiler chickens. The analytical model used in this research is a descriptive analysis of marketing channels from producers to consumers and an analysis of marketing efficiency. The results showed that there were five marketing distribution channels. Distribution channel 1 consisted of plasma farmers, core companies, wholesalers, intermediate traders, retailers, and consumers. Distribution channel 2 consisted of plasma farmers, core companies, wholesalers, intermediate traders, and consumers. Distribution channel 3 consisted of plasma farmers, core companies, wholesalers, retailers, and consumers. Distribution channel 4 consisted of plasma farmers, core companies, wholesalers, and consumers. Distribution channel 5 consisted of plasma farmers, core companies, intermediate traders, retailers, and consumers. The marketing margins for distribution channels 1, 2, 3, 4 and 5 were IDR 2,250/kg, IDR 1,600/kg, IDR 1,200/kg, IDR 1,500/kg, and IDR 1,950/kg, respectively.